1999
DOI: 10.1037/0021-9010.84.6.925
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing strain and maximizing learning: The role of job demands, job control, and proactive personality.

Abstract: Using a sample of 268 production employees, this study extended research on R. Karasek's (1979) demands-control model of stress in 2 ways. First, results show that R. Karasek's proposed interaction between demands and control when predicting strain occurred only for more proactive employees. This 3-way interaction helps reconcile previous inconsistent findings about the interaction between demands and control when predicting strain. Second, the study extends research by investigating the demands-control intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
300
5
18

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 386 publications
(346 citation statements)
references
References 44 publications
16
300
5
18
Order By: Relevance
“…Recently, Griffin and colleagues (in press) found that leader vision in combination with high levels of role breadth self-efficacy led to significant increases in proactivity one year later. Parker and Sprigg (1999) showed that job control mitigated the stressful effects of high job demands for employees who were high in proactive personality but not for those who are more passive (interaction of β=-.12, p<.01). The researchers argued that proactive employees take advantage of high levels of job control to manage their job demands more effectively, whereas passive employees do not make good use of autonomy and so high levels of job demands lead to higher levels of strain irrespective of the level of job control.…”
Section: Interactions Between Individual and Situational Antecedentsmentioning
confidence: 99%
“…Recently, Griffin and colleagues (in press) found that leader vision in combination with high levels of role breadth self-efficacy led to significant increases in proactivity one year later. Parker and Sprigg (1999) showed that job control mitigated the stressful effects of high job demands for employees who were high in proactive personality but not for those who are more passive (interaction of β=-.12, p<.01). The researchers argued that proactive employees take advantage of high levels of job control to manage their job demands more effectively, whereas passive employees do not make good use of autonomy and so high levels of job demands lead to higher levels of strain irrespective of the level of job control.…”
Section: Interactions Between Individual and Situational Antecedentsmentioning
confidence: 99%
“…Energy spent in dealing with the emotional consequences of heavy workloads and chronic strain can seriously decrease one's resources to respond effectively to job demands, thereby provoking higher levels of emotional exhaustion and consequently affecting performance (Karasek, 1979;Parker & Sprigg, 1999;Taris, 2006). It is in the nature of proactive people to energetically engage the environment and alter it to get things done.…”
Section: Emotional Exhaustionmentioning
confidence: 99%
“…Since its emergence in the early 1990s, PP has gained momentum as a valid construct and a predictor of relevant outcomes, including organizational performance (Crant, 1995), work adjustment (Kammeyer-Mueller & Wanberg, 2003), the ability to deal with occupational constraints (Parker & Sprigg, 1999), and leadership performance (Crant & Bateman, 2000). PP has also been linked with actual advancements in salary and position (Seibert et al, 1999;Seibert et al, 2001), job search success (Brown, Cober, Kane, Levy, & Shalhoop, 2006), organizational citizenship behavior (Parker, 1998), career success (Seibert et al, 2001), and team effectiveness (Kirkman & Rosen, 1999).…”
Section: Proactive Personality and Affective Commitmentmentioning
confidence: 99%